ANALISIS GUGATAN WANPRESTASI DI PENGADILAN NEGERI GIANYAR (STUDI KASUS NOMOR 95/PDT.G/2024/PN GIN) - Ni Luh Martini (Nusantara Hasana Journal, 2025)
The distric court, as an institution authorized to handle the settlement of cases, plays an importan role in resolving default lawsuits. Based on Article 1234 of the Civil Code, a party who feels aggrieved has the right to file a lawsuit based on the fault or promise of another party in fulfilling its obligations. The porpuse of this paper is to find out how the analysis of the judge’s decision in a default lawsuit at the Gianyar Distric Court and what are the factor causing default in the agreement. This paper is compiled using the normative method. Where this study aims to analyze the Decision of the Gianyar Distric Court Jugde No. 95/Pdt.G/2024/PN Gin regarding the default case.